2018
DOI: 10.1016/j.ajpath.2018.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Glypican 3 Overexpression across a Broad Spectrum of Tumor Types Discovered with Functional Genomic mRNA Profiling of a Large Cancer Database

Abstract: Glypican 3 (GPC3), a membrane-bound heparan sulfate proteoglycan, is overexpressed in approximately 70% to 80% of hepatocellular carcinomas, but is not expressed commonly in healthy tissues. This raised interest in GPC3 as a drug target and several GPC3-targeting drugs are in clinical development. We therefore predicted GPC3 protein overexpression across tumors and validated these predictions. Functional genomic mRNA profiling was applied to the expression profiles of 18,055 patient-derived tumor samples to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 36 publications
(19 reference statements)
4
40
0
Order By: Relevance
“…Moreover, it has been reported that the high expression of NCAPH in tumor tissues of patients with colon cancer had a significantly better prognosis and survival rate than patients with low expression [34]. As for the intersection of the key gene set and key target genes, it is noteworthy that although GPC3 had not been used as the final independent prognostic indicator, it also confirmed the GPC3 over-expression in a variety of cancers [35]. LRRK2 was amplified and overexpressed in papillary renal and thyroid carcinomas in the study [36].…”
Section: Discussionmentioning
confidence: 91%
“…Moreover, it has been reported that the high expression of NCAPH in tumor tissues of patients with colon cancer had a significantly better prognosis and survival rate than patients with low expression [34]. As for the intersection of the key gene set and key target genes, it is noteworthy that although GPC3 had not been used as the final independent prognostic indicator, it also confirmed the GPC3 over-expression in a variety of cancers [35]. LRRK2 was amplified and overexpressed in papillary renal and thyroid carcinomas in the study [36].…”
Section: Discussionmentioning
confidence: 91%
“…Functional genomic mRNA profiling has been reported as an aid to diagnose intratumoral GPC3 expression for such cancers with a low frequency of GPC3 expression . Moek et al reported a relative difference of ≤10% in 28 of 34 tumor types for which functional genomic mRNA data could be compared with the results of IHC analysis. This is a promising result, suggesting a useful method as a biomarker for predicting GPC3 expression in various carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…GPC3 is expressed in various fetal tissues (ie, liver, lung, kidney, and placenta), but is not observed in normal postnatal tissues; however, GPC3 is expressed in HCC, melanomas, ovarian clear cell carcinoma, and in certain childhood cancers (hepatoblastomas, nephroblastomas, and yolk sac tumors) . Recent immunohistochemistry (IHC) studies have suggested that GPC3 can also be expressed in other tumors, including gastric cancer, colorectal cancer, non‐small cell lung cancer, thyroid cancers, renal cancer, bladder cancer, and breast cancer …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, breast cancer was found to upregulate glypican-1 [120] and syndecan-4 [121] and to downregulate glypican-3 [122], whereas low expression of glypican-3 promotes tumor proliferation and metastasis [123]. Contrarily, glypican-3 was found to be overexpressed in approximately 70% to 80% of hepatocellular carcinomas [124] and high glypican-5 expression levels in non-small cell lung cancer were associated with poor differentiation, vascular invasion, regional lymph node metastasis, and a higher TNM stage (TNM classification of malignant tumors) [125]. In addition, glypican-2 is upregulated in neuroblastoma and associated with poor overall survival [117].…”
Section: Expression Of Hspgs In Tumorigenesismentioning
confidence: 99%